OP0292 Different Pain Trajectories in Early Symptomatic Knee OA; 5 Year Follow-Up of Check (Cohort Hip & Cohort Knee) Study. (23rd January 2014) - Wesseling, J.; Bastick, A. N.; Bierma-Zeinstra, S. M.; Bijlsma, J. W.
Abstract : Objectives: Knee pain is often the first sign of knee OA and it is known that its course can be very different between patients over time. This study identifies distinct groups of patients with different trajectories of pain due to symptomatic knee OA, and describes lifestyle and coping characteristics for each trajectory of pain. Lifestyle factors might be important elements for prevention, since they are modifiable in nature. Yet de role of lifestyle factors in different pain trajectories in early OA is unclear. Methods: Longitudinal data of five years follow-up of the CHECK study was used. Participants had pain of knee or hip, were aged 45-65 years, and had not yet consulted their physician for these symptoms or the consultation occurred within 6 months before inclusion. Pain severity was measured with numeric scale (0-10). Latent class growth analysis identified homogenous subgroups with distinct trajectories of pain. Multinomial regression analysis was used to examine different lifestyle and coping characteristics between the trajectories Results: Longitudinal data of 5 years follow-up of 705 participants with symptomatic knee OA was analyzed. Three pain trajectories were identified based on their outcome: good, moderate and poor outcome. Participants with good outcome trajectory (n=222) had over time a slight decrease in pain severity and ended up with a low pain severity. Participants with moderate outcome trajectory (n=294) had a stable course of moderate pain over time. The poor outcome trajectory participants (n=189) had an increase of pain severity over time and ended up with severe pain. Compared to the good outcome group, participants in the moderate and poor outcome group were characterized by higher BMI (both OR's 1.1; p=0.01), smokers (moderate outcome group OR=1.8, p=0.08; poor outcome group OR= 2.5, p=0.01) used passive coping strategies worrying (moderate outcome group OR= 2.2, p=0.01; poor outcome group OR=3.5, p<0.001) and resting (moderate outcome group OR= 1.6, p=0.09; poor outcome group OR=2.4, p=0.004). The passive coping strategy 'retreating' reduced the chance of belonging to the poor outcome group (moderate outcome group OR= 0.6, p=0.04; poor outcome group OR=0.5, p=0.009). Conclusions: This study identified 3 trajectories of pain: good, moderate and poor outcome. Unhealthy lifestyle characteristics (high BMI and smoking) and passive coping strategies (worrying and resting) characterized the poor outcome group. Distinguishing different trajectories could have implications for the treatment. Treatment for each pain trajectory in early OA might be tailored to lifestyle and coping characteristics. Acknowledgements: CHECK-cohort study is initiated by the Dutch Arthritis Association and performed within; Erasmus Medical Center Rotterdam; Kennemer Gasthuis Haarlem; Leiden University Medical Center; Maastricht University Medical Center; Martini Hospital Groningen /Allied Health Care Center for Rheum. and Rehabilitation Groningen; Medical Spectrum Twente Enschede /Ziekenhuisgroep Twente Almelo; Reade, formerly Jan van Breemen Institute/ VU Medical Center Amsterdam; St.Maartens-kliniek Nijmegen; University Medical Center Utrecht and Wilhelmina Hospital Assen Disclosure of Interest: None Declared